Vowel-Zero Alternation in Root-Final Obstruent–Sonorant Clusters in Modern Bulgarian: Is [ə] an Epenthetic Vowel or a Vocalised Yer?. (3rd July 2021) - Hristovsky, Gueorgui
ABSTRACT: This article proposes two tests that allow us to determine, first, whether the root-final [ə] in obstruent–sonorant clusters is alternating or not and, second, if alternating, whether the surfacing [ə] is an epenthetic vowel or a vocalised yer. The correct underlying representations are necessary for any subsequent analysis of related forms with strings of alternating vowels and for the better understanding of the contexts and conditionings of these alternations. At the same time, different root types are identified, and rule analysis of yer vocalisation is proposed: yers vocalise to the left or to the right of unsyllabified consonants. This approach also allows us to decide which will be the default case in the underlying representations of items which cannot be submitted to the second test.